EUS Guided Gastroenterostomy Vs Surgical Gastrojejunostomy for the Palliation of Malignant Gastric Outlet Obstruction: : A Systemic Review and Meta-analysis (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Gastroenterology; Research